PENINGKATAN KESEJAHTERAAN PETANI DENGAN KONSEP GREEN ECONOMY LIMBAH BUAH JERUK NIPIS (Citrus aurantifolia) SEBAGAI BAHAN POMADE ANTI KETOMBE - Oryza Sativa, Rima Dewi; Wahyu Budiman, Eko; Febrianti, Neha (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2024)
Pomade is a styling material that is usually used by men with strong adhesion and a shiny finish. The potential of the lime part, especially lime waste as a natural hair care combined with mixed ingredients such as olive oil, castor oil, can be produced in the form of pomade hair oil. The purpose of this study is to find out the use of lime waste to improve the economy of farmers, to know the advantages and marketing strategies of lime waste treatment products. This activity is in collaboration with lime farmers of the "Sidowayah" Farmers Group, so that farmers can improve their welfare and productivity with the concept of Green Economy of lime waste. The method used in this study is agricultural business analysis and marketing strategy. The calculation of the R/C ratio of 1.296 (value >1) shows that lime pomade is profitable and worthy of being used as a business. The profit obtained based on the calculation of farming analysis is Rp. 57,150 for 10 production processes or Rp. 5,715 for 1 piece of lime pomade packaging. This lime pomade product has also been laboratory tested for Vitamin C content and Fe levels. This vitamin C activity test stage is a vitamin determination to determine the level of vitamin C (ascorbic acid) in orange, lime, and vitamin samples with iodometric titration. Laboratory results showed that every 100 mg contained 0.025 Vitamin C. Meanwhile, the laboratory results of Fe content contained in every 100 mg of lime extract sample were 3.92. Based on the results of this study, lime pomade is very feasible to be developed as a product that can improve the economy of lime farmers.